Perbandingan Peningkatan Hasil Belajar Kimia dan Biologi Melalui Penggunaan Alat Peraga di SMP Satu Atap Wasur Merauke - Henie Poerwandar Asmaningrum (LPPM Universitas Negeri Jakarta, 2017)
This study aims to determine the comparison of increased learning outcomes of chemistry and biology through the use of props. This research uses experimental research method. The population in this study is all students of class VIII SMP Satu Atap Wasur Merauke. The technique of collecting data with Test, documentation and observation techniques. Data analysis technique used is correlation Test. The results showed that the mean value of the learning outcomes after using the props was better than before using props (74.6129> 59.1290) and the mean value of biological learning outcomes after using props better than before using props (75.2903> 59.4839). That result supported by the value of t-Test of two parties wherein the chemistry learning result tcount <ttable (-59,144 <-2,04227) and on the biology study result tcount <ttable (-86.802 <-2,04227). This study concludes that there are differences in the results of chemistry and biology learning through the use of visual aids, where the average value of chemistry and biology learning results is increased after using props. Keywords: Learning achievement, props, chemistry, biology